Confirming the involvement of PIEZO2 in the etiology of Marden–Walker syndrome. Issue 3 (27th December 2020) - Seidahmed, Mohammed Zain; Maddirevula, Sateesh; Miqdad, Abeer M.; Al Faifi, Abdullah; Al Samadi, Abdulmohsen; Alkuraya, Fowzan S.
Abstract: Pathogenic heterozygous variants in PIEZO2 typically cause distal arthrogryposis type 5 (DA5) and the closely related Gordon syndrome (GS). Only one case of PIEZO2 ‐related Marden–Walker syndrome (MWS) has been reported to date. We report the phenotypic features of a Saudi female patient with features consistent with MWS in whom we identified a novel de novo likely pathogenic variant in PIEZO2 . Our case lends support to the link between PIEZO2 and MWS.